Respuesta :
Answer:
x³ + 11x² + 28x
Step-by-step explanation:
(x + 4)(x² + 7x)
Each term in the second factor is multiplied by each term in the forst factor, that is
x(x² + 7x) + 4(x² + 7x) ← distribute parenthesis
= x³ + 7x² + 4x² + 28x ← collect like terms
= x³ + 11x² + 28x
[tex] \huge \underline{ \sf \: Solution}[/tex]
[tex](x + 4)( {x}^{2} + 7x) \\ = x( {x}^{2} + 7x) + 4( {x}^{2} + 7x) \\ = {x}^{3} + {7x}^{2} + {4x}^{2} + 28x \\ = {x}^{3} + {11x}^{2} + 28x [/tex]
[tex]\huge\underline{\sf Answer:}[/tex]
[tex]{x}^{3} + {11x}^{2} + 28x [/tex]